BENCANA ALAM DALAM PERSPEKTIF AL-QUR’AN DAN BUDAYA MADURA - Achmad Muhlis (Institut Agama Islam Negeri Madura)
Abstrac:Natural disasters occurring in this country always effect a deep grief to the people. Despite the fact that a number of rhetoric have been reconstructed to overcome the disaster from new order up to reformation order. Unfortunately, this is not supported by a concrete action. The questions are that weather the disaster is either an admonition or a punishment given by Allah? Why Allah rebukes this country so terribly. This short paper is about to disclose the meaning behind the disaster from the view point of al-Qur’anKeyword:bencana alam, murka Allah, tolak bala’